Application Of Discovery Learning Model To Improve Science Learning Outcomes of Electric Circuit Material In Class VI SD Muhammadiyah Sukorejo - Wahyu Setyoningsih (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The background of this classroom action research is the low learning outcomes of science learning in class VI SD Muhammadiyah Sukorejo. Of the 25 grade VI students only 4 children completed (16%) and 21 other children did not complete (84%) measured by the completeness of student learning outcomes (KKM: 65.00). This classroom action research (PTK) consists of two cycles and each cycle consists of 2 meetings consisting of four stages, namely planning, implementing, observing and reflecting.The purpose of this study was to determine the amount of improvement in science learning outcomes in electrical circuit material. In this study, the action taken was learning using the discovery learning model in science learning with electrical circuit material in class VI SD Muhammadiyah Sukorejo students in semester 1 of the 2020/2021 academic year. The data obtained in this study were analyzed using comparative descriptive by comparing quantitative data from cycle I and cycle II. Based on the results of the study showed that student learning outcomes from the initial conditions an average value of 61 with completeness of 16%. This condition experienced an increase in the average score of students in the first cycle, which was 69 and the percentage of completeness was 60%. In the second cycle there was an increase of 82 again with a completeness percentage of 88%, so that the predetermined performance indicator of 75% has been achieved. Thus it can be concluded that the application of discovery learning models in learning can improve science learning outcomes of electrical circuit material in grade VI students of SD Muhammadiyah Sukorejo semester 1 of the 2020/2021 academic year.